Errata: Communications - Scientific letters of the University of Zilina, 2022, 24(3), p. B228-B238, https://doi.org/10.26552/com.C.2022.3.B228-B238, Prediction of the ultra-large container ships' propulsion power at the initial design stage - Korlak, Piotr Kamil (Communications - Scientific Letters of the University of Zilina, 2023)
Errata: Communications - Scientific letters of the University of Zilina, 2022, 24(3), p. B228-B238, https://doi.org/10.26552/com.C.2022.3.B228-B238, Prediction of the ultra-large container ships' propulsion power at the initial design stage
Keywords: Errata; 2022; 24(3); p. B228-B238; https://doi.org/10.26552/com.C.2022.3.B228-B238